Neuroprotective effects of curculigoside against Alzheimer’s disease via regulation oxidative stress mediated mitochondrial dysfunction in L-Glu-exposed HT22 cells and APP/PS1 mice - Wenqi Wang; Yidi Qu; Siyu Li; Jinyu Chu; Hongxin Yang; Lirong Teng; Di Wang (Food Science and Human Wellness)
Curculigoside (CCG) is a phenolic glycoside compound extracted from the root of a natural plant called Curculigo orchioides Gaertn. In this study, the neuroprotective effect of CCG through oxidative stress mediated mitochondrial dysfunction on L-glutamate (L-Glu)-damaged hippocampal neuron cell line (HT22) and APPswe/PSEN1dE9 transgenic (APP/PS1) mice were investigated. Observably, CCG in L-Glu-damaged HT22 cells suppressed apoptosis, reduced the accumulation of reactive oxygen species, balanced the mitochondrial membrane potential and prevented the over-influx of calcium. In APP/PS1 mice, 4-week CCG administration significantly improved their memory and behavioral impairments, enhanced the function of cholinergic system, reduced the deposition of Aβ and neurofibrillary fiber tangles caused by tau phosphorylation, and suppressed the development and progression of oxidative stress in brains of APP/PS1 mice. Based on the screening of proteomic analysis on hippocampus, CCG were confirmed that it could regulate the expression levels of proteins related to mitochondrial dysfunction, mainly through activating on AMPK/Nrf2 signaling, in APP/PS1 mice and L-Glu-exposed HT22 cells. CCG has a prominent neuroprotective effect on regulate the AMPK/Nrf2-mediated mitochondrial dysfunction in cells APP/PS1 mice support CCG is a potentially potent drug for AD treatment and merits further investigation.